Connectivity Mapping Using a Novel sv2a Loss-of-Function Zebrafish Epilepsy Model as a Powerful Strategy for Anti-epileptic Drug Discovery - Zhang, Yifan; Heylen, Lise; Partoens, Michèle; Mills, James D.; Kaminski, Rafal M.; Godard, Patrice; Gillard, Michel; de Witte, Peter A. M.; Siekierska, Aleksandra (Frontiers in Molecular Neuroscience, 2022)
Synaptic vesicle glycoprotein 2A (SV2A) regulates action potential-dependent neurotransmitter release and is commonly known as the primary binding site of an approved anti-epileptic drug, levetiracetam. Although several rodent knockout models have demonstrated the importance of SV2A for functional neurotransmission, its precise physiological function and role in epilepsy pathophysiology remains to be elucidated. Here, we present a novel sv2a knockout model in zebrafish, a vertebrate with complementary advantages to rodents. We demonstrated that 6 days post fertilization homozygous sv2a-/- mutant zebrafish larvae, but not sv2a+/- and sv2a+/+ larvae, displayed locomotor hyperactivity and spontaneous epileptiform discharges, however no major brain malformations could be observed. A partial rescue of this epileptiform brain activity could be observed after treatment with two commonly used anti-epileptic drugs, valproic acid and, surprisingly, levetiracetam. This observation indicated that additional targets, besides Sv2a, maybe are involved in the protective effects of levetiracetam against epileptic seizures. Furthermore, a transcriptome analysis provided insights into the neuropathological processes underlying the observed epileptic phenotype. While gene expression profiling revealed only one differentially expressed gene (DEG) between wildtype and sv2a+/- larvae, there were 4386 and 3535 DEGs between wildtype and sv2a-/-, and sv2a+/- and sv2a-/- larvae, respectively. Pathway and gene ontology (GO) enrichment analysis between wildtype and sv2a-/- larvae revealed several pathways and GO terms enriched amongst up- and down-regulated genes, including MAPK signaling, synaptic vesicle cycle, and extracellular matrix organization, all known to be involved in epileptogenesis and epilepsy. Importantly, we used the Connectivity map database to identify compounds with opposing gene signatures compared to the one observed in sv2a-/- larvae, to finally rescue the epileptic phenotype. Two out of three selected compounds rescued electrographic discharges in sv2a-/- larvae, while negative controls did not. Taken together, our results demonstrate that sv2a deficiency leads to increased seizure vulnerability and provide valuable insight into the functional importance of sv2a in the brain in general. Furthermore, we provided evidence that the concept of connectivity mapping represents an attractive and powerful approach in the discovery of novel compounds against epilepsy.